High‐Performance Flexible Silicon Nanowire Field Effect Transistors on Plastic Substrates - Ting Zhang; Ying Sun; Ruijin Hu; Wentao Qian; Linwei Yu (Advanced Electronic Materials)
Abstract Inorganic semiconductor nanowires, known for their exceptional electronic properties and mechanical flexibility, are widely regarded as the ideal 1D channel materials for creating high‐performance flexible electronics. In this work, the integration of ordered arrays of silicon nanowire (SiNW) field effect transistors (FETs) directly onto flexible plastic substrates is showcased. The self‐aligned crystalline SiNW multi‐channels are first grown through an in‐plane solid–liquid–solid mechanism on rigid substrates, and then efficiently transferred in‐batch onto flexible polyethylene terephthalate (PET) plastics. The FETs constructed on these transferred SiNW channels exhibit outstanding performance, with a high on/off current ratio of >105, a low subthreshold swing of 175 mV dec−1, and remarkable mechanical stability that can endure an extremely small bending radius of 0.5 mm for 1000 cycles. Furthermore, inverter logics are also successfully demonstrated on plastic substrates, highlighting a prominent routine for scalable integration of high‐quality SiNW channels in the development of low‐cost, high‐performance flexible displays and wearable electronics.